Applying FIGS to crop wild relatives and landraces in Europe - Thormann, I. (PGR secure, 2012)
The Focused Identification of Germplasm Strategy (FIGS) (Mackay and Street, 2004) emerged as an approach to target accessions more likely to possess specific genetic variation sought by breeders. FIGS was a collaborative development involving researchers from the International Centre for Agricultural Research in the Dry Areas (ICARDA), the Australian Winter Cereals Collection and the Russian N.I. Vavilov Research Institute of Plant Industry. It involves gathering available information and knowledge to facilitate the identification of candidate accessions. Geographic information system (GIS) tools and statistical and modelling techniques can then be used to select the candidate accessions for evaluation, based on an understanding of relationships between traits and the environment.